1999
DOI: 10.1094/mpmi.1999.12.6.508
|View full text |Cite
|
Sign up to set email alerts
|

The Ambivalence of the Barley Mlo Locus: Mutations Conferring Resistance Against Powdery Mildew (Blumeria graminis f. sp. hordei) Enhance Susceptibility to the Rice Blast Fungus Magnaporthe grisea

Abstract: Recessive alleles of the barley Mlo locus confer non-race-specific resistance against the powdery mildew fungus Blumeria graminis f. sp. hordei (Bgh). Recently the Mlo gene has been isolated and it was suggested that the Mlo product is a negative regulator of cell death. Thus, loss of function can precondition cells to a higher responsiveness for the onset of multiple defense functions. Here, we document an enhanced susceptibility of barley mlo mutants to the rice blast fungus Magnaporthe grisea. The disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 29 publications
9
140
2
1
Order By: Relevance
“…Both Arabidopsis mlo2 and barley mlo plants exhibit enhanced disease symptoms toward necrotrophic and hemibiotrophic pathogens (7,16,17), and a number of the coexpressed genes also have a known role in defense against these classes of pathogens (Dataset S6). Therefore, we tested a subset of the insertion lines for their responses to the necrotrophic fungi Alternaria brassicicola and Botrytis cinerea.…”
Section: Identification Of Novel Genes Required For Defense Against Dmentioning
confidence: 99%
“…Both Arabidopsis mlo2 and barley mlo plants exhibit enhanced disease symptoms toward necrotrophic and hemibiotrophic pathogens (7,16,17), and a number of the coexpressed genes also have a known role in defense against these classes of pathogens (Dataset S6). Therefore, we tested a subset of the insertion lines for their responses to the necrotrophic fungi Alternaria brassicicola and Botrytis cinerea.…”
Section: Identification Of Novel Genes Required For Defense Against Dmentioning
confidence: 99%
“…Barley plants carrying a loss of function mutation at the Mlo locus are completely resistant to all known isolates of Bgh but behave hypersusceptible to M. oryzae and Bipolaris sorokiniana. [14][15][16] It has already been shown that silencing of Mlo using transient-induced gene silencing based on biolistic transgene delivery phenocopied the resistance of mlo-mutant plants against Bgh. 17 But to our knowledge this approach hasn't been addressed for barley using VIGS so far.…”
Section: Mlo-silencing As a Case Studymentioning
confidence: 99%
“…Recessive mutants of Mlo in both barley and Arabidopsis are resistant to adapted mildew species (Panstruga, 2005), which indicates that this form of resistance cannot be negated by adapted pathogen effectors. However, whereas mlo mutations are ineffective against rusts (Jorgensen, 1992) and mlo mutant barley is more susceptible than the wild type to the rice blast pathogen M. grisea (Jarosch et al, 1999), the PEN1 pathway in Arabidopsis appears to be specific against mildew species (Shimada et al, 2006). A challenge for molecular genetics will be to identify genes analogous to Mlo for combating these pathogens through activation of prehaustorial defenses.…”
Section: Can Components Of Nonhost Resistance Be Engineered To Contromentioning
confidence: 99%